2017
DOI: 10.53761/1.14.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Teaching how to Listen. Blended Learning for the Development and Assessment of Listening Skills in a Second Language

Abstract: This paper discusses the integration and effectiveness of blended learning for the development and assessment of listening skills in a second language. The development of oral abilities (listening and speaking) is one of the most challenging and neglected aspects of second language learning (Vandergrift & Goh 2012, Graham & Santos 2015). Listening comprehension work in particular is crucial in the early stages of second language acquisition, and, therefore, for ab-initio language students, for whom pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Previous studies displayed two major themes, namely, experience of learners on learner autonomy and motivation ( Garrison and Kanuka, 2004 ; Ige and Hlalele, 2017 ; Anthony et al, 2019 ; Dolores et al, 2019 ), and the impact on the language ability, including reading, writing, listening, and vocabulary of learners ( Caruso et al, 2017 ; Kazakoff et al, 2018 ). Regarding the first theme, studies focus on the experience of learners, examining how blended learning has the potential to enhance both the effectiveness and efficiency of meaningful learning experiences ( Garrison and Kanuka, 2004 , p. 95).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies displayed two major themes, namely, experience of learners on learner autonomy and motivation ( Garrison and Kanuka, 2004 ; Ige and Hlalele, 2017 ; Anthony et al, 2019 ; Dolores et al, 2019 ), and the impact on the language ability, including reading, writing, listening, and vocabulary of learners ( Caruso et al, 2017 ; Kazakoff et al, 2018 ). Regarding the first theme, studies focus on the experience of learners, examining how blended learning has the potential to enhance both the effectiveness and efficiency of meaningful learning experiences ( Garrison and Kanuka, 2004 , p. 95).…”
Section: Literature Reviewmentioning
confidence: 99%
“… Kazakoff et al (2018) confirmed that the blended learning approach contributed to the development of reading ability in learners of English. Likewise, Caruso et al (2017) discussed the integration and effect of blended learning on the development and assessment of listening skills in a second language. In addition, Miyazoe and Anderson (2010) delved into the effect of blended courses on learning outcomes and perceptions of students to online writing with the employment of three different online writing tools in an English as a foreign language (EFL) blended learning setting, and the results suggested a positive effect on the language learning progress of students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As it is a popular contemporary approach in language teaching, researchers have put emphasis on investigating the effectiveness of it in teaching and learning and learners' perceptions/attitudes towards it. As for EFL teaching, there have been various studies in the literature investigating the use of blended learning in teaching of the language skills and sub-skills (eg., for listening : Caruso, Colombi & Tebbit, 2017;Tran & Ma, 2021; for speaking: Wang, 2020; for reading: Bataineh & Mayyas, 2017; for writing : Challob, Bakar & Latif, 2016; for grammar: Al-Bataineh, Banikalef & Albashtawi, 2019; for vocabulary: Ebadi & Ghuchi, 2018). Majority of the studies have resulted that blended learning has positive effects on learners' performances in the related skills.…”
Section: Implementation Of Blended Learning In Efl Teachingmentioning
confidence: 99%
“…In the study conducted by Caruso et al (2017), the researchers have investigated the effects of blended learning on the learners' listening skill in Italian. Instead of face-to-face mode, the students had online listening quizzes in which they could have the chance to do the tasks in quizzes through multiple access enabling them to study in a flexible way.…”
Section: Implementation Of Blended Learning In Efl Teachingmentioning
confidence: 99%
“…In addition, many researchers in this field (Roussel et al, 2019; Vandergrift and Goh, 2012) observe the predominance of teachers testing learners listening comprehension as compared with teaching students how to process listening input. As Caruso et al (2017) posit, one of the main problems associated with current approaches is that listening comprehension has focused solely on testing students to listen to audio tracks and indeed according to Kok (2018), language learners either receive little help from their teachers or are left to take care of their listening skills by themselves. This study contributes to filling the gap as suggested by both Caruso et al (2017) and Kok (2018) in adding to research that will have an impact on teaching practices.…”
Section: Introductionmentioning
confidence: 99%